(untitled) (Herald of Journalism, 2020)
In the paper studied a representative sociological information sources in Kazakhstan. Considered the topics and types of publications in the me- dia of Kazakhstan, based on the results of sociological research. Showed examples of sociological publications created in the genres: sociological summary, rating, analytical interview, article. Analyzed the reasons for the ambiguous attitude to sociological publications in the media of Kazakh- stan from the audience and experts.